Association between infection and nutritional status among infants in a cohort study of vitamin A in western Kenya - Grant, Frederick K.; Wanjala, Rose; Low, Jan; Levin, Carol; Cole, Donald C.; Okuku, Haile S.; Ackatia-Armah, Robert; Girard, Amy W. (Frontiers in Nutrition, 2022)
Background: Infection is associated with impaired nutritional status especially of infants under 5-years. Objectives: We assessed the impact of infection indicated by both the acute phase proteins (APP), C-reactive protein (CRP) and α-1-acid-glycoprotein (AGP), and as reported by maternal recall, on the nutritional status of infants. Methods: 505 pregnant-women were enrolled into a nested-longitudinal-cohort study of vitamin A (VA). Data from 385 children are reported here.. Incidence and severity of respiratory infection and diarrhea (previous 14 days) were assessed by maternal recall; infant/child feeding practices were collected. Infant weight, recumbent-length and heel-prick capillary blood were taken at 9-months postpartum. Indicators of VA status [(retinol binding protein (RBP)], iron status (Hb, ferritin) and subclinical inflammation APP, CRP (>5mg/L) and AGP (>1g/L), were determined. Impacts of infection on infant nutritional status were estimated with logistic regression models. Results: Infection prevalence, based on elevated CRP and AGP levels, was 36.7%. For diarrhea reported symptoms, 42.4% of infants at 9-months had no indication of infection as indicated by CRP and AGP; for acute respiratory reported symptoms, 42.6% had no indication of infection. There was a significant positive association with infection among VA deficient (RBP<0.83µmol/L) infants based on maternal reported symptoms but not with iron deficiency (ferritin<12µg/L). The odds of having infection, based on increased CRP and AGP, in underweight infants was 3.7 times higher (OR: 3.7; 95% CI: 2.3, 4.5; P=0.019). Infants with iron deficiency were less likely (OR: 0.40; 95% CI: 0.1, 0.7; P=0.001) to have infection based on CRP and AGP, whilst infants with VA deficiency were 5 times more likely (OR: 5.06; 95% CI: 3.2, 7.1; P=0.0001) to have infection. Conclusions: APP are more useful in defining infection in a population compared to reported symptoms of illness. Not controlling for inflammation in a population while assessing nutritional status might result in inaccurate prevalence estimation.